2017
DOI: 10.24200/sci.2017.4348
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of functionally graded stiffened micro-cylinder based on the modified couple stress theory

Abstract: Abstract. In this paper, free vibration of the micro-cylinder made by functionally graded material that is stiffened in circumferential direction, has been investigated based on the modified couple stress and first order shear deformation theories. Modified couple stress theory (MCST) has been used to catch size effects in micro scales. By using first order shear deformation theory and Hamilton principle, general equations of motion and corresponding boundary conditions have been derived. Free vibration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Rafaeinejad et al showed clearly the e ects of foundation, gradient index, aspect ratio, and nonlocal parameter on stability and vibration analysis. More recently, Jabbarian and Ahmadian conducted the free vibration analysis of a functionally graded sti ened micro-cylinder [104]. They took the size e ect into consideration using the Modi ed Couple Stress Theory (MCST).…”
Section: Continuum Models Of Nanostructuresmentioning
confidence: 99%
“…Rafaeinejad et al showed clearly the e ects of foundation, gradient index, aspect ratio, and nonlocal parameter on stability and vibration analysis. More recently, Jabbarian and Ahmadian conducted the free vibration analysis of a functionally graded sti ened micro-cylinder [104]. They took the size e ect into consideration using the Modi ed Couple Stress Theory (MCST).…”
Section: Continuum Models Of Nanostructuresmentioning
confidence: 99%
“…The classical continuum mechanics theories are unable to explain and predict the mechanical behavior of the materials in small sizes. Therefore, some of the non-classical continuum theories such as strain gradient theory, couple stress theory, nonlocal elasticity theory, and surface elasticity theory have been introduced to capture the size e ect on elastic deformation behavior of micro-structures [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%